(untitled) (Experimental biology, 2026)
This article investigates the hyperspectral characteristics of barley. A major challenge in agriculture is the inability to perform early disease diagnosis. Hyperspectral imaging enables the identification of diseases at an early stage, preventing their further spread. Spectral analysis of barley diseases (loose smut, leaf spot, root rot) shows that infected and dried tissues have low reflectance, early-stage infections exhibit medium reflectance, and healthy tissues display high spectral intensity. In hyperspectral images, diseased plant areas appear blue, areas with living but already infected tissue appear yellow, and healthy plant areas are shown in orange, red, and burgundy. Spectra from healthy areas possess high intensity compared to those from diseased zones. This is attributed to the presence of chlorophyll, the green pigment in healthy tissue that actively reflects light. The destruction of the epidermis, loss of moisture, tissue necrosis, and darkening lead to a decrease in reflected light intensity.